Heard it through the Grapevine ‐ Social Network Analysis of a Hydrology Class. (August 2016) - Hernandez, E. Annette; Uddameri, Venkatesh
Abstract: Social network analysis (SNA) was investigated as an efficient way to understand the dynamics behind collaborative endeavors and group formation in project based courses. The SNA was applied to a junior level undergraduate engineering hydrology class with two sections taught by two professors with varying levels of structure. It was found that students tended to use formal sources of information (i.e., professor, teaching assistant, textbook, or class notes); however, the use depended on the amount of structure in the class. More independent students did not collaborate in assigned groups, preferring to self‐select study groups. Furthermore, the less structured class created a split atmosphere of "connected" students who had many interactions as well as "disconnected" students on the other end of the spectrum. The more structured class created fewer but more even distribution of interactions between students. The SNA study corroborated that collaborations correlate positively with class grade. In fact, those students with fewer interactions with their classmates performed poorly in the class.